Understanding the Impact of Artificial Intelligence on Students’ Speaking Proficiency: A Lecturer's Perspective - Muhammad Bambang Purwanto; Anggra Prima; Ridayani Ridayani; Aisyah Aisyah; Fahrur Rozi (Language and Education Journal, 2026)
The rapid integration of Artificial Intelligence (AI) in higher education has transformed English language teaching, particularly in developing students’ speaking proficiency. This study explores English lecturers’ perceptions of AI use in speaking instruction at STIAB Smaratungga Boyolali, a Buddhist higher education institution in Central Java, Indonesia. Employing a qualitative descriptive design with a phenomenological approach, five lecturers were purposively selected as participants. Data were collected through semi-structured interviews, classroom observations, and document analysis, and analyzed using a thematic analysis approach. The findings reveal that lecturers generally hold positive perceptions of AI, recognizing its role in enhancing students’ confidence, fluency, and pronunciation, while emphasizing that AI functions as a supplementary tool rather than a replacement for teachers. Lecturers also identified challenges, including limited infrastructure, ethical concerns, and the need for digital literacy and pedagogical training. AI-assisted activities, such as self-practice, chatbot conversations, and project-based learning, were found to foster autonomous learning and active student engagement. This study contributes to the understanding of the pedagogical potential and limitations of AI in English-speaking instruction, offering insights for curriculum design, teacher development, and the responsible integration of technology in higher education.